An improved chromosome-level genome assembly and annotation of Hong Kong catfish (Clarias fuscus) - Yu Chen; Xinghua Lin; Dayan Zhou; Yulei Zhang; Qian Wang; Huapu Chen; Dongneng Jiang; Siping Deng; Guangli Li; Peipei Wang; Changxu Tian (Scientific Data)
Abstract Clarias fuscus, renowned for its resilience and nutritional value, is a significant aquaculture species in China. To facilitate further genetic research and breeding programs in this species, we generated an improved high-quality chromosome-level genome assembly of a female C. fuscus using MGI, PacBio, and Hi-C sequencing technologies. The final genome assembly spans 982.84 Mb, with contig and scaffold N50 values of 36.16 Mb and 37.66 Mb, respectively, and successfully anchors 99.60% of the sequences to 28 pseudochromosomes. We also predicted 24,849 protein-coding genes, with 97.3% of them functionally annotated. BUSCO analysis indicates a completeness of 97.03% for the assembly and 96.6% for the annotation. This study significantly advances the genomic resources available for C. fuscus and supports future molecular breeding and functional genomics research.